Urgensi Shared Responsibility System dalam Manajemen Hakim - Aprillia, Rizti (Jurnal Konstitusi, 2022)
Discourse regarding the management of judges in Indonesia continues to emerge, especially triggered by the change of judge status from originally civil servants to state officials. In addition, the one-stop-system factor which still leaves a lot of problems gives birth to new ideas, namely the Shared Responsibility System concept or distribution of authority in judge management which the Draft is now being formulated by the DPR in the form of a draft bill on the position of judges. In many countries, the concept is commonly practiced and in line with the theory of checks and balances between state institutions in order to realize justice accountability. The research used to discuss these problems is juridical normative with a prescriptive research typology. The type of data used in this study is secondary data. The study results concluded that it is necessary to think of a way out as a new concept in improving judicial management. The solution offered was that the management of judges to be no longer carried out by one institution, but requires the involvement of other institutions.